Proximate analysis of animal feed from organic waste and effect on changes in body weight Gallus domesticus - Muhammad Rijal (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The purpose of the study was to find that solid waste from sago, tofu, and rice could be made into animal feed with high nutritional content as evidenced by increasing body weight of Gallus domesticus.Method: This research is a quantitative research using laboratory and field experimental methods to examine the proximate feed and the reaction of experimental animals during feeding. The proximate profile of feed was determined using indicators (protein, carbohydrate, fat, calcium, vitamin B-12, carotene/vitamin A content, ash content, and water content), and the experimental animals’ response to feeding was determined using time indicators. The reaction of experimental animals to feed was determined using a stopwatch, as shown by the amount of time spent feeding.Results: The results showed that each type of feed had a different proximate profile, with the highest levels of protein, fat, ash, and water found in animal feed made from tofu waste; levels of calcium, vitamin B-12, and vitamin A content are found in animal feed made from a combination of tofu dregs and sago dregs. The highest carbohydrate content was observed in animal feed made from sago dregs. The results of the one-way ANOVA test showed that there was a difference in body weight gain and FCR of Gallus domesticus after being given feed from organic waste, where the best feed was made from tofu waste.Conclusion: Each type of organic waste feed has a different proximate profile, where Gallus domesticus responds very well to all feeds, and has an effect on chicken body weight.